The Influence of Perceived Benefit, Perceived Risk, and Financial Literacy on Continuance Intention to Use E-Wallets in Financial Transactions - Khoirul Hikmah; Revika Novrita Putri; Diana Anggraini Kusumawati (Journal of International Conference Proceedings, 2025)
The purpose of this research is to determine the influence of perceived benefit, perceived risk, and financial literacy on continued intention to use e-wallets. The population in this study was all active undergraduate students of the UPN "Veteran" Yogyakarta Management Study Program who used e-wallets. The sample determination method used a purposive sampling method with a sample size of 97 respondents. This research uses the SPSS software program, and the data analysis techniques used are descriptive statistical analysis and multiple linear regression analysis. The results of the research show that (1) perceived benefit, perceived risk, and financial literacy together have a significant effect on continuance intention, (2) perceived benefit and financial literacy partially have a positive and significant effect on continuance intention, while perceived risk partially has a negative and significant effect on continuance intention